Representation of Female Footballers in Interviews on PSSI TV: A Critical Discourse Analysis - Aulli Reza Atmam (JCommsci - Journal Of Media and Communication Science, 2021)
Sports is inseparable from gender inequality and is attached to masculine image even though nowadays the two things are fading, particularly, in the realm of football. In Indonesia, female footballers are increasingly starting to exist not only on the field but also in the media, one of which is on the PSSI TV YouTube channel which shows videos of exclusive interviews with female footballers. This study examines how female footballers are represented in the video interview. Using the Sara Mills’ Critical Discourse Analysis (CDA) method, it is known that female footballers who are the interviewees are positioned as both the subject and object of narrating and being narrated. Meanwhile, the representation of female footballers which is reflected emphasizes on two things, namely the ones who uphold gender equality and professionalism. The interviewees also make use mediation with a dominantly showing portion in media and several cultural codes to represent themselves.   Keywords: sports;  football;, female footballer; critical discourse analysis